Hubungan antara Tipe Kepribadian Big Five dengan Terpaan Berita Viral di Platform Media Sosial - Ladya Ghaisani K; Indy Rahma F; Dilla Maghdalena O; Abdullah Azzam Al Afghani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The rapid development of digital technology, especially social media, makes access to information easier and faster. The development of increasingly sophisticated technology allows individuals to obtain news from various sources anytime and anywhere, one of which is through social media. Social media has become a staple part of the lives of today's younger generation. The research design used is quantitative research. The design used in this research is inferential statistics. The sampling method in this study used purposive sampling technique. This study successfully revealed a significant relationship between the personality dimensions of Extraversion and Conscientiousness with the tendency of individuals to be exposed to viral news on social media. Individuals who are more Extraversion tend to be less interested in sensational news, while Conscientiousness tend to actively seek information, including viral news.